Organizational Culture Orientations and Employee Turnover Rate among Star Rated Hotels in Nairobi County - Onyango, Beatrice; Otieno Obonyo, George; Chepngetich, Beatrice (International Journal of Scientific Research and Management (IJSRM), 2022)
Hospitality industry is characterised by intensity of labour all over the world. Curiously, the sector is also dodged with higher employee turnover and slow growth, with many ventures closing down annually. In Kenya, the employee turnover rate remains at over 50% with hotels in Nairobi recording the highest turnover of over 72% by the first quarter of the year 2021. Management scholars have argued that aligning organizational culture to the business environment is the best approach to dealing with organization outcomes, including employee turnover. The main objective of this study was to investigate the influence of organizational culture orientations on employee turnover rate among star rated hotels in Nairobi County. Specific objectives were to determine the influence of innovation orientation culture on employee turnover rate, and to establish the influence of stability orientation culture on employee turnover rate. Contingency theory, which stipulates that approaches for enhancing firm outcome are contingent upon environmental factors was adopted. The study employed a correlational survey design on a target population of 486 top and middle-level managers. Fishers et al (1998) formula and multistage sampling were used to select a sample of 213 from the target population. Data was collected via structured questionnaires. Expert rating method was used to calculate a content validity index (CVI) of 0.88 for the instrument. Reliability was calculated through split-half method, where correlation coefficients of 0.88, and 0.84 for organizational culture and organizational structure respectively was attained. Descriptive and inferentialwereusedfordataanalysis. The findings showed that 75.7% changes in employee turnover rate is attributed to organizational culture orientations investigated by the study (R2 =0.757). Findings also showed that stability orientation (β=0.473), and innovative orientation (β=0.484) all are significant predictors {F (1, 183) =278.617, P